A dual‐band reconfigurable filtering antenna using PIN diodes for WiMAX and WLAN applications. Issue 12 (28th September 2022) - Das, Sangeeta; Sarkar, Pankaj
Abstract: The realization of a compact dual band reconfigurable filtering antenna is described for WiMAX and WLAN application through this communication. First and foremost, a dual band filter is offered employing four open ended half wavelength Stepped Impedance Resonators (SIRs) to resonate at 3.2 GHz and 5.35 GHz. PIN diodes have been connected to the edges of the innermost resonators to switch the operation from dual passband to two different single passbands and to all stop configuration. Multipath coupling helps to create transmission zeroes on either side of passband enriching the selectivity. In order to implement the filtering antenna, a compact monopole antenna is presented using two triangular radiating patches radiating at 3.2 GHz and 5.35 GHz. Finally, the filter and the antenna structures are combined to accomplish the proposed dual band reconfigurable filtering antenna. The results with reference to return loss and radiation pattern are provided and good performances are obtained. The suggested filtering antenna has the reflection coefficient lower than −16 dB for all the desired operating bands. As well, it offers gain of about 3.21 dBi and 5.08 dBi at the two radiating bands. The developed prototype is fabricated and measured to examine the anticipated and simulated results where a close agreement is established between them.